2017
DOI: 10.1371/journal.pone.0175525
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hepatitis C virus in adult population in the Czech Republic – time for birth cohort screening

Abstract: Chronic hepatitis C is curable disease. Low detection rate could be one of the reasons of poor treatment uptake. It is important to identify HCV prevalence and anti-hepatitis C virus (HCV) positive patients in population by effective screening strategy such as risk-based or birth cohort screening programs. There are no national population-based estimates of the HCV prevalence in the Czech Republic (CZ). The most recent seroprevalence survey determined a prevalence of positive anti-HCV antibodies of 0.2% (in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
31
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 19 publications
5
31
0
1
Order By: Relevance
“…However, Saxena et al34 reported a high rate of anemia in patients with severe renal impairment treated with full-dose SOF even in those without RBV addition. The epidemiology of HCV infection has changed during the last decade in our region; the prevalence of genotype 3 rose from <5% to 45% 35. In agreement with the changing epidemiology of HCV, our patients infected with genotype 3 were younger and had a shorter period of hemodialysis and fewer comorbidities in comparison with our historical group of patients infected with genotype 1b 36.…”
Section: Discussionsupporting
confidence: 81%
“…However, Saxena et al34 reported a high rate of anemia in patients with severe renal impairment treated with full-dose SOF even in those without RBV addition. The epidemiology of HCV infection has changed during the last decade in our region; the prevalence of genotype 3 rose from <5% to 45% 35. In agreement with the changing epidemiology of HCV, our patients infected with genotype 3 were younger and had a shorter period of hemodialysis and fewer comorbidities in comparison with our historical group of patients infected with genotype 1b 36.…”
Section: Discussionsupporting
confidence: 81%
“…Furthermore, a 2018 study in Mongolia showed similar rates where 77% of the positive individuals were aged >50 years 15 . In contrast, in the Czech Republic, the prevalence of anti-HCV-positive cases was 1.6%, and the lowest prevalence was observed in individuals aged ≥60 years (0.2%; n=2) 16 . These differences can be explained by the exposure of the different populations to various risks factors.…”
Section: Discussionmentioning
confidence: 79%
“…In the present study, we found that, of anti-HCV-positive individuals with tattoos and piercings, 29.6% were born in the 1970s. In a study in the Czech Republic, of 525 individuals with tattoos and piercings, 3.8% were HCV positive; however, the age group was not disclosed, and no evidence of a relationship between this factor and infection was found 16 . A study on 2637 individuals in Valencia, Spain, found that antibody detection was positive in 30 individuals (1.1%).…”
Section: Discussionmentioning
confidence: 94%
“…Also, in the Netherlands, there was no effect of birth cohort on the prevalence of HCV infection when screening was offered to patients born between 1948 and 1978 in a primary care setting, even though the study was performed in two hot spots for HCV (prevalence >1%) . A seroprevalence study in the Czech Republic in 2015 did identify a birth cohort with a higher HCV prevalence, namely patients born between 1971 and 1985 . In Spain, seroprevalence was 1.6% in patients born between 1949 and 1974 who visited the hospital for a colonoscopy …”
Section: Discussionmentioning
confidence: 99%
“…36 A seroprevalence study in the Czech Republic in 2015 did identify a birth cohort with a higher HCV prevalence, namely patients born between 1971 and 1985. 37 In Spain, seroprevalence was 1.6% in patients born between 1949 and 1974 who visited the hospital for a colonoscopy. 38 The effect of age and gender found in the present study could have been influenced by higher proportions of PWID and imprisonment in certain groups.…”
Section: Discussionmentioning
confidence: 99%